Unlocking Student Writing Potential: Exploring Genre-Based Learning in the English Classroom - Sholihah, Risma Zahrotus; Prastikawati, Entika Fani; Wahyuni, Sri (Universitas Pahlawan Tuanku Tambusai, 2025)
Writing remains one of the most challenging skills for Indonesian English as Foreign Language (EFL) learners, particularly at the secondary education level. This study investigates the effectiveness of Genre-Based Learning (GBL) in enhancing students’ writing abilities and explores their learning experiences throughout the instructional process. Employing a mixed-methods pre-experimental design, the research involved 32 eleventh-grade students from SMA PGRI 1 Pati who participated in an eight-session GBL intervention following the Building Knowledge of the Field (BKOF), Modelling of Text (MOT), Joint Construction of Text (JCOT), and Independent Construction of Text (ICOT) cycle. Data were collected through pre-test and post-test writing assessments focusing on narrative and analytical exposition texts, complemented by student learning journals completed after each session by a purposively selected subsample of 18 students who demonstrated significant performance variations. Quantitative analysis using paired sample t-tests revealed significant improvement in students' writing across five key components: content development, structure, grammar, vocabulary, and coherence. Qualitative thematic analysis of student reflections indicated enhanced confidence, understanding of text structures, and motivation to write, though some challenges with complex grammatical forms persisted. Findings suggest that GBL offers effective scaffolding for Indonesian EFL learners, fostering genre awareness and writing competence while supporting positive learning experiences.